Effect of Mn substitution for Co on the structural, kinetic, and thermodynamic characteristics of ZrCo1−xMnx (x=0–0.1) alloys for tritium storage. (23rd November 2017) - Weng, Chengcai; Xiao, Xuezhang; Huang, Xu; Jiang, Fulei; Yao, Zhendong; Li, Shouquan; Ge, Hongwei; Chen, Lixin
Abstract: ZrCo1− x Mn x ( x  = 0–0.1) alloys for tritium storage were prepared by induction levitation melting under an argon atmosphere. The effect of Mn substitution for Co on the alloy microstructure, initial activation behavior, hydrogen storage kinetics and thermodynamics was investigated. The results show that the ZrCo1− x Mn x ( x  = 0, 0.025, 0.05) alloys have a single phase of ZrCo, while ZrCo1− x Mn x ( x  = 0.075, 0.1) alloys consist of a main phase of ZrCo and a secondary phase of ZrMn2 . It is observed that the initial activation time (uptake to 95% of saturated hydrogen capacity) decreases from 63.73 h to 0.24 h as the Mn content increases from x  = 0 to x  = 0.1. However, Mn substituted for Co is determined to result in disproportionation during activation and a loss in hydrogen capacity. For increasing Mn content in the alloy, the plateau width for Pressure-Composition-Temperature (P-C-T) curve is shortened, while the plateau pressure remains mostly unchanged. DSC measurements were also performed to investigate the thermal stability of the ZrCo1− x Mn x system. Highlights: The effects of Mn substitution for Co in the ZrCo1− x Mn x were investigated. The initial activation behavior of ZrCo1− x Mn x is improved with increasing Mn. Co substituted with Mn results in the disproportionation during the activation.